"Communis Hostis Omnium": The Smerwick Massacre (1580) and the Law of Nations. (July 2019) - Orr, D. Alan
Abstract: This article examines the brutal massacre of up to six hundred Spanish and Italian papal troops on the order of the English Lord Deputy Arthur Grey, 14th Baron de Wilton (1536–1593), at Dún An Óir (Forto del Oro), Smerwick, County Kerry, on 10 November 1580. The article investigates the relationship between the religious and juridical rationales for the massacre, shedding new light on the broader relationship between the early modern law of nations, Protestantism, and what Brendan Bradshaw has characterized as "catastrophic violence" in the Elizabethan military conquest of Ireland. While Vincent Carey has emphasized the virulently anti-Catholic character of Grey's rationales for the massacre, my argument instead emphasizes the role of the received laws of nations and of war in justifying Grey's actions both to Queen Elizabeth I (1533–1603) and to the English public, from the period immediately following the massacre until the writing of Edmund Spenser's pro-Grey apologetic, A View of the Present State of Ireland (ca. 1596). On this view, the papal troops at Smerwick were considered brigands, pirates, or, in Marcus Tullius Cicero's words, "communis hostis omnium"—a common enemy to all—and enjoyed no standing as lawful enemies under the law of nations. In the sixteenth century, the established law of nations was hardly a seamless web but manifested significant cleavages and fissures allowing for the construction of localized spheres of legal exception in which the ordinary rules of warfare did not apply, thus providing a convenient juridical rationale for atrocity.